Inertia friction welding of large steel piston with 480 mm diameter used in heavy-duty diesel engine components - Wu, Yanquan; Qin, Feng; Zhang, Chunbo; Wang, Zhiyong; Li, Rui; Yang, Haifeng; Wang, Dali; Tong, Yiqi; Zhou, Jun (Frontiers in Materials, 2026)
IntroductionInertia friction welding (IFW) has emerged as a critical solid-state joining technology for manufacturing high-performance steel pistons in heavy-duty diesel engines, particularly where complex hollow geometries and stringent reliability requirements preclude conventional fusion welding. However, its application to large-scale components—such as pistons exceeding 450 mm in diameter—remains underexplored, especially regarding the interplay among joint geometry, thermal–mechanical history, and resulting microstructure–property relationships.MethodsThis study demonstrates the successful IFW of a Ø480 mm forged 42CrMo steel piston. A systematic investigation was conducted on the microstructural evolution and mechanical integrity of both the inner (thick-walled) and outer (thin-walled) weld zones, leveraging metallographic analysis, hardness testing, and tensile characterization to correlate processing conditions with performance outcomes.ResultsGeometric asymmetry between the thick inner and thin outer walls induced markedly different cooling rates during welding, leading to distinct microstructures and mechanical responses. Both weld zones exhibited excellent tensile ductility; however, their strength–ductility trade-offs were microstructurally governed. The inner weld showed localized embrittlement due to rapid cooling-induced banded phases and grain-boundary carbides, whereas the outer weld benefited from more favorable thermal conditions that promoted dynamic recrystallization and phase stability. Consistent flash formation across both interfaces confirmed robust process control.DiscussionThese findings validate the technical feasibility of scaling IFW to large-diameter steel pistons for next-generation heavy-duty engines. Moreover, they highlight how joint geometry directly influences thermal management during welding, thereby offering a design lever to tailor microstructure and mechanical performance. This work provides fundamental insights to support the broader adoption of solid-state welding in high-value, safety-critical powertrain applications.